The Role of Bines Dance in Matchmaking Among The Gayo Tribe: A Phenomenological Study - Nabila Jaratun Nisa; Toni Nasution (MASI Mandiri Edukasi, 2025)
This study examines the evolving role of the Bines Dance in the matchmaking traditions of the Gayo community in Southeast Aceh. Initially performed as an interlude to the Saman Dance, the Bines Dance has developed into a meaningful cultural practice, particularly within the bejamu Saman tradition, where it serves as a subtle platform for courtship between local female dancers (seberu) and male visitors (tetamu). Using a qualitative, phenomenological approach, this research explores the lived experiences of individuals involved in or affected by the dance. Data were gathered through participant observation, in-depth interviews, and documentation, involving 15 informants: cultural leaders, dancers, matchmaking facilitators, and community members. Findings reveal that the Bines Dance acts as a poetic form of indirect communication. Female dancers express romantic interest through structured rhymes and metaphorical verses, initiating a symbolic exchange known as najuk. This tradition allows emotional expression while adhering to customary norms. The offering of a money ring (cincin uang) by the male guest’s family to the dancer marks a shift toward serious intent, often culminating in arranged meetings and marriage. The study concludes that the Bines Dance functions not only as entertainment but also as a living cultural mechanism for relationship-building and social cohesion. It reflects the community’s values while adapting to modern contexts, highlighting the importance of preserving traditional art as a dynamic force within Gayo society.